'Stubbornly unchanged': A longitudinal study of news practices in the Israeli press. (June 2014) - Reich, Zvi
The article summarizes three consecutive studies (2001, 2006, 2011) in which national Israeli press reporters detailed how they obtained random samples of their recently published items ( N = 1003): first, in order to explore the public interest in whether the standards of news production are deteriorating, improving or staying put; second, to indicate whether journalists adjust to the transforming news ecosystem; and third, to resolve the theoretical dilemma regarding the openness of news practices to change. While showing a general trend of conservatism, data indicate some statistically significant changes across time, not always in the expected directions. Reporters rely more often on ordinary citizens (who remain a marginal source), and public relations practitioners intervene more broadly in their items. They not only question their sources' credibility more often, but also rely on slightly more sources per item and more cross-checking, mainly thanks to older contacts rather than to new voices.